Otonomi Desa dalam Pengembangan Badan Usaha Milik Nagori (BUMNAG) di Nagori Cingkes, Kabupaten Simalungun - Nava Arella Ginting, Netanya; Februati Trimurni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Village autonomy is a form of decentralization that grants villages the authority to manage community interests based on original rights and local values. In this context, Badan Usaha Milik Nagori (BUMNag) plays a vital role in supporting economic independence through the sustainable utilization of local resources, as mandated by Law Number 6 of 2014 concerning Villages. However, the development of BUMNag in Nagori Cingkes still encounters various challenges, including technical limitations, weak institutional capacity, and low community participation. This study employs a qualitative descriptive method to explore the dynamics of BUMNag’s development in Nagori Cingkes. Data were collected through in-depth interviews, field observations, and document studies involving village officials, BUMNag administrators, and local community members. The analysis is based on the theory of village autonomy by H.A.W. Widjaja (2003), which emphasizes the village's right, authority, and obligation to manage its resources independently and responsibly. The findings reveal that while village autonomy has been initiated through the establishment and management of BUMNag, its development remains limited. Business operations are currently focused only on the clean water sector, while other potentials such as agriculture and tourism remain untapped. Although basic services are being provided, BUMNag’s economic contribution is still minimal due to the absence of significant profit generation. Therefore, it is recommended that the Nagori Cingkes government diversify BUMNag’s business units, improve human resource capacity through training, develop business plans based on local potentials, and increase community participation to realize sustainable village-owned enterprise development.